Iron Behavior in Nickel Laterite Inverse Leaching Process - K. Jiang; S. Liu; K. Xie; L. Su (Canadian Institute of Mining, Metallurgy and Petroleum, 2016)
The reduction of iron dissolution and acid consumption is fairly important in the extraction of Ni and Co from laterite ores from both economic and efficiency perspectives. BGRIMM conducted detailed research to investigate the behavior of iron in a nickel laterite leaching process. The mineralogy of Ni and Co was studied. In limonite ore about 76% of nickel is present in goethite while in saprolite ore 79% of nickel is associated with magnesium and silicon minerals. Test work revealed that limonite can be decomposed completely with enough acid concentration during atmospheric leaching. More than 98% of Ni and Co were leached into solution while 85% of the iron was also dissolved with 130-140 g/L iron in solution. Iron precipitates as hematite in the temperature range 250-270?C without neutralization reagents. That’s why limonite is treated by high pressure acid leaching (HPAL) technology to achieve nickel extraction and iron precipitation in the same autoclave. BGRIMM’s test results indicated that the remaining acid in atmospheric leaching solution and acid released by iron precipitation at a lower temperature was enough to leach saprolite efficiently. The so-called inverse leaching technology leaches limonite at atmospheric condition and the leaching slurry combined with saprolite is pumped into an autoclave to leach saprolite at 150-170?C. In the autoclave iron precipitates as hematite without acid consumption. Total nickel and cobalt extractions in the test program were more than 90% with iron content in solution below 8 g/L. In this inverse process iron dissolves in the atmospheric leaching stage and precipitates as hematite in the low temperature leaching stage. Compared with HPAL the leaching temperature is reduced to 150-170 ºC from 250-270 ºC. Compared to atmospheric tank leaching acid consumption is reduced from 850-950 kg/t ore (atmospheric) to 550-650 kg/t ore (inverse).